HOW TO CREATE SPEAKING POLITENESS IN ELEMENTARY SCHOOL OF SDN 101788 MARINDAL 1 MEDAN - Dharyana Suryadijaya; Rahma Yunita Ansi; Dian Anggraini Harahap; Datulina Ginting; Derliana Hasibuan (JURNAL EDUSCIENCE, 2023)
This research aims to describe and analyze the form of politeness language in conversation classroom. Interaction between the students and the teachers. The approach which is used qualitative descriptive. Thi at s research activity uses data collection methods, namely competent free involvement methods, and notes. Data of this research is the language expressions in the form of words and sentences of the speakers. The data source of this research is used oral data source in the form of speech event between the speakers, namely between the students to their teachers. The politeness language for an interaction with the teachers in classroom learning is very dominant in the three modes of speech, they are 1) request; 2) application; and 3) expect. Asking is a directive politeness act that has the goal of expecting the speech partner to be given something as requested by the speaker.Key Words : Politeness, Politeness Language, Students, Teachers.Â AbstrakPenelitian ini bertujuan untuk menjelaskan dan mengkaji kesopanan berbicara dalam bahasa Inggris, khususnya interaksi antara siswa dan guru di kelas bahasa Inggris. Pendekatan yang digunakan adalah deskriptif kualitatif. Pendekatan dan catatan keterlibatan kompeten independen digunakan untuk mengumpulkan data untuk penelitian ini. Ungkapan bahasa berupa kata-kata dan kalimat penutur merupakan data penelitian. Sumber data lisan yang digunakan dalam penelitian ini adalah tindakan berbicara antara penutur, khususnya siswa dan guru. Etiket bahasa mendominasi interaksi dengan dosen dalam tiga bidang: 1) permintaan, 2) implementasi, dan 3) harapan. meminta adalah kesantunan pribadi yang mengharapkan lawan bicara menyampaikan sesuatu sesuai permintaan penutur.Kata kunci: kesantunan, kesantunan berbahasa, siswa, guru.